2011
DOI: 10.1007/s10658-011-9772-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analysis of Peronosclerospora (Oomycetes) reveals cryptic species and genetically distinct species parasitic to maize

Abstract: Downy mildews are amongst the most widespread and economically important pathogens of cultivated grasses in the tropics and subtropics. Despite their importance, molecular methods, particularly DNA sequence analysis, have rarely been applied to either species identification or to the determination of phylogenetic relationships between species. Here we report the presence of several cryptic species in the genus Peronosclerospora. Further we confirm that maize can be parasitised by several species of Peronoscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 42 publications
0
44
0
9
Order By: Relevance
“…Molecular phylogenetic reconstruction based on partial cox2 (Cytochrome c oxidase subunit II gene) and nrLSU (nuclear ribosomal large subunit) sequences showed two distinct clades of undescribed species of Peronosclerospora infecting Sorghum species that are native to northern Australia (Telle et al 2011). In this present study, we have morphologically re-examined those specimens and described two distinct novel species.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Molecular phylogenetic reconstruction based on partial cox2 (Cytochrome c oxidase subunit II gene) and nrLSU (nuclear ribosomal large subunit) sequences showed two distinct clades of undescribed species of Peronosclerospora infecting Sorghum species that are native to northern Australia (Telle et al 2011). In this present study, we have morphologically re-examined those specimens and described two distinct novel species.…”
Section: Introductionmentioning
confidence: 65%
“…Conidiophores and conidia not seen on the type host. Previous DNA sequence analysis (Telle et al 2011) showed that P. australiensis also infected S. plumosum and maize. Sorghum timorense and S. plumosum are closely related and difficult to differentiate because both have leaves that senesce during the dry season.…”
Section: Results and Taxonomymentioning
confidence: 99%
See 3 more Smart Citations